The Influence of E-Procurement, E-Payment, and E-Commerce on Supply Chain Performance in the Development of Digitalization Innovation at Coffee Shops/Cafes in Surabaya - Suryono, Muhammad Zacky; Palupi, Ghea Sekar (Universitas Negeri Surabaya, 2024)
This study examines the influence of digitalization on supply chain performance in coffee shops in Surabaya. The research aims to determine whether digitalization has a positive impact on supply chain performance in coffee shops in Surabaya. The study employs a quantitative method based on data from respondents from coffee shops that utilize digitalization. The analysis method used in this study is Structural Equation Modeling (SEM). The results show that e-procurement technology enables coffee shops to purchase raw materials online, while e-payment facilitates customers to make online payments. The results of e-commerce technology can increase operational efficiency, reduce costs, and enhance service quality. Therefore, e-procurement, e-payment, and e-commerce technology can help coffee shops in Surabaya develop digital innovation and improve supply chain performance.